1981
DOI: 10.1136/adc.56.12.939
|View full text |Cite
|
Sign up to set email alerts
|

Eczema and atopy in early childhood: low IgA plasma cell counts in the jejunal mucosa.

Abstract: SUMMARY Twenty-one children aged between 2 and 54 months, 14 with eczema and 7 with allergies in first-degree relatives, were referred for diagnostic jejunal mucosal biopsy for a variety of symptoms. A partial villous atrophy was found in 19 of the 21 biopsies obtained; the other 2 were normal. We report a highly significant (P Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 7 publications
0
14
0
1
Order By: Relevance
“…These have included histological and functional abnormalities of the gastric epithelium,1 mild degrees of jejunal villous atrophy with eosinophil infiltration and oedema of the lamina propria,1 2 low jejunal mucosal IgA plasma cell counts,3 and increased IgE immunoreactive cells in the duodenal mucosa 4. There have also been a number of reports of increased gastrointestinal permeation by inert markers such as lactulose and rhamnose 5…”
mentioning
confidence: 99%
“…These have included histological and functional abnormalities of the gastric epithelium,1 mild degrees of jejunal villous atrophy with eosinophil infiltration and oedema of the lamina propria,1 2 low jejunal mucosal IgA plasma cell counts,3 and increased IgE immunoreactive cells in the duodenal mucosa 4. There have also been a number of reports of increased gastrointestinal permeation by inert markers such as lactulose and rhamnose 5…”
mentioning
confidence: 99%
“…The respiratory and gastrointestinal tracts are the main affected organs [6,7,8]. IgA-deficient patients may be frequently affected by allergies, the most common of which is asthma followed by allergic rhinitis, conjunctivitis, urticaria, atopic dermatitis and food allergies [6,9]. Autoimmune diseases associated with SIGAD include immune thrombocytopenic purpura, autoimmune hemolytic anemia (AIHA), rheumatoid arthritis, lupus erythematosus, thyroiditis and vitiligo [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for this are unknown, but other immunological compensations might provide sufficient or complete restitution. IgA deficiency was found to be strongly associated with allergic diseases, including asthma, allergic rhinitis/conjunctivitis, urticaria, atopic dermatitis, and food allergies, [18][19][20][21][22]36 but the underlying mechanisms are not yet understood. It has been shown that the majority of these patients also have deficiency of secretory IgA.…”
Section: Discussionmentioning
confidence: 99%
“…1,5,7,[14][15][16][17] Immunoglobulin A (IgA) deficiency has been found to be associated with many allergies, including asthma, allergic rhinitis, urticaria, atopic dermatitis, and food allergies. [18][19][20][21][22] However, in the literature there are no studies about the prevalence of Ig deficiency in children with VKC. In this study, our aim was to determine the demographic characteristics, clinical features, prevalence of systemic atopy, and Ig deficiencies in Turkish patients with VKC.…”
mentioning
confidence: 99%